2011
DOI: 10.1088/0951-7715/24/3/001
|View full text |Cite
|
Sign up to set email alerts
|

On charge-3 cyclic monopoles

Abstract: Abstract. We determine the spectral curve of charge 3 BPS su(2) monopoles with C 3 cyclic symmetry. The symmetry means that the genus 4 spectral curve covers a (Toda) spectral curve of genus 2. A well adapted homology basis is presented enabling the theta functions and monopole data of the genus 4 curve to be given in terms of genus 2 data. The Richelot correspondence, a generalization of the arithmetic mean, is used to solve for this genus 2 curve. Results of other approaches are compared.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Concerning the numerical calculation of the analytical expressions, the complete elliptic integrals can very efficiently be computed by using the arithmetic geometric mean. This can be generalized to genus two hyperelliptic integrals, see [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the numerical calculation of the analytical expressions, the complete elliptic integrals can very efficiently be computed by using the arithmetic geometric mean. This can be generalized to genus two hyperelliptic integrals, see [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Although the examples 1, 2 (for n ≥ 3), 6, 7 are for reducible curves and so outwith the theorem, they too are transcendental. The final curve has C 3 symmetry and quotients over a genus 2 curve [6]. The transcendence of the periods here requires Theorem (3.1); a genus 2-variant of the AGM due to Richelot may be used for their computation.…”
Section: Examplesmentioning
confidence: 99%
“…By using Humbert theory and results of O. Bolza we showed that only the tetrahedrally symmetric monopole in this family satisfied Hitchin's third constraint. By enlarging the class of curves to the general 3 symmetric charge-three curve, Victor, Antonella D'Avanzo (one of my students) and I were able to construct those curves associated with monopoles and provided a new family of examples [7]. Unfortunately the curve is described in terms of a vanishing period implicitly relating coefficients of the quotient curve.…”
Section: Harry Bradenmentioning
confidence: 99%